GLP-catalyzed H4K16me1 promotes 53BP1 recruitment to permit DNA damage repair and cell survival. Issue 21 (15th October 2019) - Lu, Xiaopeng; Tang, Ming; Zhu, Qian; Yang, Qiaoyan; Li, Zhiming; Bao, Yantao; Liu, Ge; Hou, Tianyun; Lv, Yafei; Zhao, Ying; Wang, Haiying; Yang, Yang; et al.
Abstract: The binding of p53-binding protein 1 (53BP1) to damaged chromatin is a critical event in non-homologous DNA end joining (NHEJ)-mediated DNA damage repair. Although several molecular pathways explaining how 53BP1 binds damaged chromatin have been described, the precise underlying mechanisms are still unclear. Here we report that a newly identified H4K16 monomethylation (H4K16me1) mark is involved in 53BP1 binding activity in the DNA damage response (DDR). During the DDR, H4K16me1 rapidly increases as a result of catalyzation by the histone methyltransferase G9a-like protein (GLP). H4K16me1 shows an increased interaction level with 53BP1, which is important for the timely recruitment of 53BP1 to DNA double-strand breaks. Differing from H4K16 acetylation, H4K16me1 enhances the 53BP1–H4K20me2 interaction at damaged chromatin. Consistently, GLP knockdown markedly attenuates 53BP1 foci formation, leading to impaired NHEJ-mediated repair and decreased cell survival. Together, these data support a novel axis of the DNA damage repair pathway based on H4K16me1 catalysis by GLP, which promotes 53BP1 recruitment to permit NHEJ-mediated DNA damage repair.